Sistem Informasi Transaksi Pembayaran Tagihan Air Di PDAM - Melin Sitorus; Desi Triani Sipayung (Bulletin of Multi-Disciplinary Science and Applied Technology, 2021)
PDAM is a regional company engaged in the management of drinking water and the management of dirty water facilities. One of the main activities in PDAM is providing services to customers. Currently, to get services regarding billing information, report stand meter numbers and report complaints against PDAM services, customers must come to the head office so that the service process is not optimal and inefficient. To provide optimal service, it is necessary to develop a better information system using information technology facilities that can be accessed by customers easily. "Information System for Water Bill Payment Transactions at PDAM" through SMS (short message service) and online payment / Online Bank Payment Point (PPOB), is expected to further improve the quality of services provided by companies to customers so that customer satisfaction levels increase and provide a positive influence on company revenue, because with SMS (short message service) customers can get services easily anywhere, anytime at a relatively cheap and efficient cost.